Review of the First Five Year Plan - Planning Commission, Government of India (Planning Commission, Government of India, 1957)
Economic Trends and Achievements, Plan Outlay and its Financing, Programme for Agriculture, Community Projects and The National Extension Services, Development of Cooperation, Animal Husbandry and Fisheries, Forests and Soil Conservation, Irrigation and Power, Industry and Minerals, Village and Small Industries
Government of India Planning Commission
Government of India Planning Commission
Keywords: First Five Year Plan- India